Open the Black Box of Autonomous Learning: A Sustainable Approach to Language Learning - Jing, Hoo Fang; Mohd Noh, Mohd Amin; Harun, Zur ‘Ain; Ibrahim, Raihan; Mohsin, Nur’ Ain (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Autonomous learning is a fundamental aspect of education that builds important skills, like critical thinking, problem-solving, and adaptability, which are important for achievement in a constantly changing professional environment. Cultivating it promotes lifelong learning, self-improvement, and knowledge beyond traditional educational settings. The objective of this study is to demonstrate the impact of the investigated autonomous learning approach to learners, and assess their ability to sustain the learning process, hence fostering lifelong learning within the framework of formal education. An Autonomous Learning Model (ALM) based 14-week qualitative study examined learners' work and reflections. Theme-based analysis was conducted with 62 fourth-semester English-language learners. A six-stage thematic analysis discovered coded responses' themes. The ALM examined the following key aspects of individual development: personal responsibility, positive self-esteem, decision-making, problem-solving, interpersonal skills, critical and creative thinking abilities, and a strong enthusiasm for learning. The results showed that autonomous learning is achievable, and that instructors’ support and institutional collaboration will improve new curriculum and courses. This study aims to enhance semester-end evaluations, leading to significant improvements for future language-programed learners and ensuring the sustainability of their learning.